Dressing Apraxia as Initial Manifestation of Creutzfeldt-Jakob Disease - Heckmann, Josef G.; Vachalova, Ivana; Vynogradova, Irina; Schwab, Stefan (Tremor and Other Hyperkinetic Movements, 2020)
Background: Creutzfeldt-Jakob disease (CJD) is a rare prion disease characterized by rapidly progressive dementia.
CRIS-Team WoS Importer:2020-07-24